Youth take the lead: Digital poetry and the next generation. (11th March 2013) - Gregory, Helen
Abstract Digital literacy projects offer an exciting means of engaging young people in poetry. Many such projects fall short of realising their full potential however, overlooking students' technological expertise and ability to learn from one another. Youth slam and spoken word (YSSW) offers possibilities for developing these projects, making creative use of both new technologies and student‐centred learning techniques. YSSW's artistic and didactic achievements demonstrate what young people can achieve if we relinquish our privileged positions as authoritative teachers/artists. This article considers how YSSW participants have used digital technologies to create innovative artworks, develop new notions of literacy and inspire their peers to explore their own artistic, socially engaged identities.